2020
DOI: 10.1002/dmrr.3423
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular disease in patients with type 1 diabetes: Early evaluation, risk factors and possible relation with cardiac autoimmunity

Abstract: Cardiovascular disease now is the leading cause of mortality among patients with type 1 diabetes (T1D). The risk of death from cardiovascular events in subjects with T1D is 2–10 times higher than the general population, depending on blood glucose control. Although complications of cardiovascular disease occur in middle and old age, pathological processes begin in childhood. Some methods used to evaluate subclinical cardiovascular disease, such as carotid intima‐media thickness and pulse wave velocity, can dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 111 publications
0
10
0
Order By: Relevance
“…In these experimental conditions, plasma from type 1 diabetic patients, but not from healthy subjects, enhanced platelet-monocyte and platelet-granulocyte binding in blood samples from healthy donors. The contribution of THPO to this priming effect is suggested by (1) the correlation analysis showing that THPO levels and leucocyte-platelet binding induced by patient plasma samples in whole blood consensually increased, and (2) the inhibitory effect of the rhTHPOR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In these experimental conditions, plasma from type 1 diabetic patients, but not from healthy subjects, enhanced platelet-monocyte and platelet-granulocyte binding in blood samples from healthy donors. The contribution of THPO to this priming effect is suggested by (1) the correlation analysis showing that THPO levels and leucocyte-platelet binding induced by patient plasma samples in whole blood consensually increased, and (2) the inhibitory effect of the rhTHPOR.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiovascular disease (CVD) is the major cause of morbidity and mortality in patients with type 1 diabetes mellitus (T1DM) [1]. The rising global incidence of T1DM with an even earlier age of onset leads to a longer exposure to the disease and a greater risk of premature CVD with microvascular and macrovascular complications that accelerate the process of atherosclerosis [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Diabetic nephropathy (DN) is a serious cardiovascular complication of diabetes mellitus, 1 which ultimately leads to end-stage renal diseases and shortens the life expectancy in diabetic patients. 2 It has been reported that one-third of individuals with diabetes mellitus develop nephropathy.…”
Section: Introductionmentioning
confidence: 99%
“…Even though clinical manifestations of cardiovascular diseases (CVDs) generally appear in adulthood, the vascular damage might start early in T1D and evidence of subclinical CVD can be detected in adolescence [ 7 ]. In addition, youth affected by prediabetes or diabetes have an increased risk of metabolic disorders in adulthood, such as hypertension, dyslipidemia, and metabolic syndrome, predisposing to CVD [ 8 ].…”
Section: Introductionmentioning
confidence: 99%